Aplicação da matemática na atividade policial: a influência que os estudos matemáticos exercem na atividade policial - SANTOS, Nivaldo Silva dos (2022)
This work addresses as a theme, the application of mathematics in police activity: the influence that mathematical studies exert in police activity. The approach is to use the computational tools, such as the Google Maps application (GPS) and the use of ARP (Drone), aiming to apply to the area of ​​public security. These technological resources contribute significantly in combating illicit trade, such as planting cannabis sativa, for example, and other branches of drug trafficking that need technology to aggregate knowledge and thus identify in areas of difficult access. To better describe the application, three problems are used that demonstrate the indispensable importance and usefulness of resources like ARP and Google Maps in gathering facts that help fight crime. The third problem will deal with the use of plane and analytical geometry in the calculation of cannabis planting area and coordinate distances in order to assess the modus operandi and how they are structured and the alleged traffickers who own the plantations are organized, using, albeit empirically, the mathematical knowledge in order to maximize the planting of the herb, which corresponds to maximum profit when the drug is benefited. The occupation of large plantation areas hardly happens, because they could be identified by a drone that visualizes regions of planting. The research concludes considering that modern technology, Google Maps, ARP, as well as mathematics in the contribution of coordinates in areas of difficult access, has been very useful in the production of knowledge, considering that these measures are essential for combating illicit trade.